The Influence of Human Resource Management (HRM) in Improving Organizational Performance - La Ode Huruhara; Herni Widiyah Nasru; Ervin Nora Susanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Human Resource Management (HRM) on organizational performance using a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. HRM in this study is proxied through several main dimensions, namely recruitment and selection, training and development, performance appraisal, and compensation systems. Meanwhile, organizational performance is measured based on aspects of productivity, operational effectiveness, and the achievement of the organization's strategic goals. Data were obtained by distributing questionnaires using a Likert scale to respondents who met the criteria as employees or active managers in various types of organizations. Analysis was conducted using SmartPLS software to test the measurement model and structural model. The results show that all dimensions of HRM have a positive and significant influence on organizational performance. This indicates that the better the implementation of HRM practices, the higher the level of organizational performance. These findings reinforce the importance of human resource management as a strategic factor in achieving competitive advantage and organizational sustainability in various sectors.